The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/w15183272
|View full text |Cite
|
Sign up to set email alerts
|

Basin-Scale Hydraulic Evaluation of Groundwater Flow Controlled Biogenic Gas Migration and Accumulation in the Central Pannonian Basin

Brigitta Czauner,
Zsóka Szabó,
Béla Márton
et al.

Abstract: Biogenic or microbial methane has an increasing share in the global gas resource base, though its exploration still faces challenges and welcomes innovations. Critical elements of its migration and accumulation models are the groundwater flows which gather and transport the gas in aqueous solution, and the seal rocks or aquifers which lead groundwater flows horizontally over great distances. This paper intends to introduce the hydraulic trap concept into these models, which is able to drive fluids horizontally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
1
1
0
1
Order By: Relevance
“…The areas are located on the southern border of the regional recharge area in the Nyírség region, where, at shallow depths (>500 m), flow-through starts to occur and become more dominant towards SW, followed by discharge conditions more to the south. This finding is consistent with the results of Szabó [39] and Czauner et al [58], who showed recharge-flow-through conditions at a shallow depth (>500 m) in the South-Nyírség region and discharge conditions to the south of the study area. Szanyi [45] also obtained similar results, showing that original flow-through existed in the South-Nyírség region, but the large water exploitation around Debrecen (a town near the study area, Figure 1b) changed the conditions to mainly recharge-dominated.…”
Section: Regional Groundwater Flow Conditions Around the Wetlandssupporting
confidence: 93%
See 1 more Smart Citation
“…The areas are located on the southern border of the regional recharge area in the Nyírség region, where, at shallow depths (>500 m), flow-through starts to occur and become more dominant towards SW, followed by discharge conditions more to the south. This finding is consistent with the results of Szabó [39] and Czauner et al [58], who showed recharge-flow-through conditions at a shallow depth (>500 m) in the South-Nyírség region and discharge conditions to the south of the study area. Szanyi [45] also obtained similar results, showing that original flow-through existed in the South-Nyírség region, but the large water exploitation around Debrecen (a town near the study area, Figure 1b) changed the conditions to mainly recharge-dominated.…”
Section: Regional Groundwater Flow Conditions Around the Wetlandssupporting
confidence: 93%
“…It appears as a transient zone first, represented by the near-hydrostatic upwelling water of the dissipated overpressure regime on the p(z) plot, as well as on the cross-section. This transient zone was identified in other parts of the Great Hungarian Plain, too [58,59]. Real overpressure values occur only at ~−2000 mBf, representing the upward-directed overpressured flow regime.…”
Section: Regional Groundwater Flow Conditions Around the Wetlandsmentioning
confidence: 74%
“…) mellett a közel hidrosztatikus nyomásviszonyok. A megújulás mértékének és pontos tartományának hidraulikai megértése azonban további kutatásokat igényel (Czauner et al 2023). Ezzel szemben a mélyebb túlnyomásos tározókba a csapadékvíz semmiképpen nem tud természetes úton bejutni, így azokról feltételezhetjük, hogy nem megújuló vizet tartalmaznak (Mádl-Szőnyi-Simon 2016; Mádlné Szőnyi,…”
Section: (2 áBra)unclassified